Analysis of the Influence of Workload and Organizational Support on Work-Life Balance with Burnot as a Mediating Variable on Gen Z Employees in E-Commerce Companies - Arbi'ah, Safrina Nur; Irmawati, Irmawati (Jurnal Ekonomi, 2026)
The aim of this study was to examine how workload and organizational support affect work-life balance, with burnout acting as a mediator. The participants included 201 Generation Z employees working in the e-commerce industry, who were selected through an online survey distributed via Google Forms. Purposive sampling was used to choose the participants. The data was analyzed using the SmartPLS method. The findings indicated that both workload and organizational support had a positive impact on work-life balance. Additionally, burnout partially influenced the relationship between workload, organizational support, and work-life balance.